Frekuensi dan Formulasi Nano Nutrien, Giberelin, dan Benzil Adenin untuk Memacu Pembungaan Anggrek Dendrobium Salaya - Mohamad Mutoharun; Tri Suwarni W.; Muzayyanah Rahmiyah (CV. Ulil Albab Corp, 2023)
The Dendrobium salaya orchid is an ornamental plant with high selling value, but there are problems with the flowering period which takes a long time. The study was to determine the effect of the frequency of formulations in the form of nanonutrients, gibberellins, and benzyl andenine purines on the flowering. The research was carried out from September to October 2022 at the Nambangan Greenhouse, Sidomulyo Village, Candimulyo District, Magelang Regency. The plan used for the study was a factorial Complete Randomized Block Design . The first factor is requency of fertilizer formulations. The second factor was in the form of fertilizer formulation treatment, the research repetition consisted of 3 blocks per treatment unit repeated 3 repetitions. Data were analyzed using Analysis of Variance. followed by the LSD test. The parameters used in this study were plant height, number of leaves, day of spike emergence, spike length, number of spikes planted, number of florets planted, number of florets per spike. The results of the study in the form of nano nutrients, gibberellins and benzyl adenine purines on the flowering showed a significant but not significant effect on the frequency of formulation administration in the Analysis of Variance followed by a further LSD test, which showed that to stimulate flowering it was sufficient to use a 1 ppm nano nutrient formulation. but if you want more optimal results on the number buds, you need to apply a 100 ppm gibberellin formulation + 100 ppm benzine adenine purine + nanonutrient 1 ppm